Wearing cultural styles in Japan : concepts of tradition and modernity in practice - Thompson, Christopher, 1962-; Traphagan, John W. (State University of New York Press, 2006)
Annotation This groundbreaking collection examines the regional dynamics of state societies, looking at how people use the concepts of urban and rural, traditional and modern, and industrial and agricultural to define their existence and the experience of living in.
Keywords: Japan -- Social conditions -- 1945-; Japan -- Civilization -- 1945-; Social change -- Japan.; Culture and globalization -- Japan.; Japon -- Conditions sociales -- 1945-; Japon -- Civilisation -- 1945-; Culture et mondialisation -- Japon.; HISTORY.; Civilization; Culture and globalization; Social change; Social conditions; Japan; Since 1945